Diversity and Threat Hunting of the Birds in the Labian-Leboyan Corridor West Kalimantan - Gusti Wicaksono; Mohamad Arif Rifqi; Imran S.L Tobing; Sri Suci Utami Atmoko (Universitas Nasional Jakarta, 2021)
Labian-Leboyan corridor is both lowland and peat swamp forested areas pointed in a strategic location between Betung Kerihun and Danau Sentarum National Park. The area is mostly managed by communities and essential areas for birds. This study is conducted to understand the diversity of birds and the threats in both peat swamp and lowland habitat using the 12 line transects method and direct observation to hunter's place. The study results are 173 bird species identified, 131 species associated with peat swamp forest, and 104 species associated with lowland forest. 108 individuals from 29 species of birds were captured for trade and meat in both habitats. Immediate conservation action is needed to support sustainable resources management of biodiversity, especially birds in the area.